Pengaruh inflasi dan jumlah uang beredar terhadap nilai tukar rupiah dengan pendekatan model struktural VAR - Tuty Alawiyah; Haryadi Haryadi; Yohannes Vyn Amzar (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2019)
The purpose of this study are, firstly to analyze exchange rate trends of rupiah, centtral bank policy rates, inflation and money supply in Indonesia from January 2019 to December 2019. Secondly, to analyzes the effect of central bank policy rate, inflation and the money supply to the rupiah exchange rate in January 2013 – Desember 2018. The method used in this research are descriptive and quantitative analysis with trend analysis tools and multiple linier regression VAR models with the Ordinary Least Square (OLS). The results of the study found that, the first trend data from the rupiah exchange rate variable of January 2019 period – December 2019 of IDR 15.145 US, the central bank’s policy interest rate was 4.5 percent, inflation was 2.15 percent and the money supply was an average of Rp.5.966.9112,17 billion. Secondly, from the processed data it was found that central bank policy rates and the money supply has a positive effect on the rupiah exchange rate of January 2013 period – December 2018. While the inflation variable has a negative impact on the rupiah exchange rate of January 2013 period – December 2018. Keywords : Rupiah exchange rate, Central bank policy interest rate, Money supply